Discovering the application of solidarity principles in the practices of savings and credit cooperatives in Tunja, Boyacá - Agudelo Gutiérrez, David Steven; Méndez Valencia, Sergio (Cooperativismo & Desarrollo, 2024)
The solidarity economy has an important position in Latin American countries. In Colombia, its recognition began in 1998 with Law 454. Solidarity organizations generate synergies that benefit their members and their environment, focusing on the common good. This study described the application of solidarity principles and their relationship with the dynamics of organization, support, management and interaction with the market of savings and credit cooperatives in Tunja framed in the solidarity economy. A qualitative method was used, collecting information through a semi-structured interview guide applied to the cooperatives' management positions. The results showed that the cooperatives comply with solidarity principles and constitutive elements. In addition, they face challenges related to the role of the State in the solidarity economy, new trends in the use of financial products by new generations, and competition between solidarity and non-solidarity financial institutions.